A provably secure dynamic ID-based authenticated key agreement framework for mobile edge computing without a trusted party. (December 2020) - Mishra, Dheerendra; Dharminder, Dharminder; Yadav, Preeti; Sreenivasa Rao, Y.; Vijayakumar, Pandi; Kumar, Neeraj
Abstract: Mobile Edge Computing (MEC) is an emergent paradigm that brings computation, storage, and network resources close to mobile users. It allows applications to execute near the user, which are delay-sensitive and content-aware. Since the MEC systems comprise distributed edge devices managed by self-governing people, they are more liable to security and privacy threats. Therefore, acure and efficient authentication mechanism is required for MEC. In this paper, we construct a mutual authentication and key agreement scheme without the involvement of a trusted third party for MEC, which ensures mutual authentication between a user and edge servers and generates a secure session key. This scheme achieves important security attributes such as secure communication, user anonymity in mutual authentication and session key agreement. The performance analysis of the proposed protocol indicates better efficiency. Moreover, we prove the security of the protocol in the random oracle model and simulate the protocols using AVISPA simulator. The analysis of security shows that the proposed protocol is safe against known attacks.